FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PHBS PENCEGAHAN PENYAKIT TB PARU PADA SANTRI DI PONDOK PESANTREN NURUL HASAN KABUPATEN MAGELANG - Fanny Ayu Ahmala Putri; Priyadi Nugraha P.; Syamsul Huda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
PHBS is a reflection of the lifestyle of a person who always pay attention and maintain his health. Pulmonary TB is an inflammatory disease of the lung parenchyma due to infection with the bacteria Mycobacterium tuberculosis. Islamic boarding school can potentially increase the incidence of Pulmonary TB if students do not maintain personal hygiene and environment.The purpose of the study to analyze the factors that influence the practice of PHBS in the prevention of pulmonary TB disease in students of boarding school Nurul Hasan.This research is a quantitative research with cross sectional approach. The population of 148 respondents. The sample uses total sampling technique. The instrument used is a structured questionnaire. The data were analyzed by univariate, bivariate using chi-square test of 95% significance level, and multivariate.Respondents were male students (57.4%) and female santri (42.6%). 94.6% of respondents in the productive age range, while 65.5% of respondents are low educated. The results showed that sex (p = 0.0001), knowledge of pulmonary tuberculosis and PHBS (p = 0.0001), attitudes toward PHBS prevention practice of pulmonary tuberculosis (p = 0,0001), facility availability (p = 0 , 0001), peer support (p = 0,0001), support of kyai (P = 0.001), support of ustadz / ustadzah (p = 0.002), cottage support (p = 0,0001), and cottage regulations (p = 0.007) is associated with the practice of PHBS in the prevention of pulmonary tuberculosis. While the variable age and level of education is not related to the practice of PHBS prevention of pulmonary tuberculosis. The result of logistic regression test showed that all variables, which most influence the practice of PHBS prevention of Pulmonary TB is the knowledge variable (OR = 13,713), other than that the support of ustadz/ustadzah (OR = 4,107) also has influence to the practice of PHBS prevention of Pulmonary TB. Islamic boarding school can enforce the regulation regarding the obligation to maintain cleanliness, specifically about personal health so that students have a reference to the implementation of personal hygiene in boarding school.